The Jurassic of North-East Greenland: Maximum Middle Jurassic transgression in East Greenland: evidence from new ammonite finds, Bjørnedal, Traill Ø - Alsen, Peter; Surlyk, Finn (Geological Survey of Denmark and Greenland, 2004)
A Middle – lower Upper Jurassic sandstone-dominated succession, more than 550 m thick, with mudstone intercalations in the middle part is exposed in Bjørnedal on Traill Ø, North-East Greenland. A number of ammonite assemblages have been found, mainly in the mudstones. Theyindicate the presence of the Lower Callovian Cadoceras apertum and C. nordenskjoeldi Chronozones. The mudstones represent northern wedges of the Fossilbjerget Formation hitherto known only from Jameson Land to the south. In Bjørnedal they interfinger with sandstones of the Pelion and Olympen Formations. The presence of the Fossilbjerget Formation in this region indicates complete drowning of the Middle Jurassic sandstone-dominated Pelion Formation during maximum Middle Jurassic transgression.A new species, Kepplerites tenuifasciculatus, is described in the appendix by J.H. Callomon. The holotype and paratype are from Jameson Land, East Greenland, but the species is also foundin Bjørnedal, Traill Ø, North-East Greenland.